Chemical Constituents and Antifeedant Activity of Essential Oils from Four Selected Malaysian Local Plants against the Invasive Red Palm Weevil Larvae - Tay, Karh Yan; Mehamod, Faizatul Shimal; Azmi, Wahizatul Afzan; Harun, Nor Omaima; Adnan, Azila; Zakeri, Hazlina Ahamad (Indonesian Journal of Chemistry, 2026)
Red palm weevil, a significant pest affecting oil palm cultivation, necessitates eco-friendly control strategies due to the environmental and health risks posed by synthetic insecticides. This study explores the efficacy of essential oils from lemongrass, gelam, pandan, and beach vitex as sustainable alternatives. Employing hydrodistillation for oil extraction, this study assessed the total phenolic content (TPC) and total flavonoid content (TFC) using gallic acid and quercetin standards, respectively. GC-MS analysis was conducted to identify the chemical constituents. The antifeedant activity was evaluated through food consumption, larval weight changes, and the feeding deterrent index (FDI) in sago food substrate experiments. Findings show oil yields of 0.42, 0.24, 0.04, and 0.03% w/w for lemongrass, gelam, beach vitex, and pandan, respectively, with gelam exhibiting the highest TPC and TFC (12.3 ± 0.36 and 10.8 ± 0.03). Significant constituents identified include beta-citral and citral in lemongrass, terpinolene in gelam, alpha-pirene in vitex, and phytol in pandan. Lemongrass and gelam displayed notable antifeedant effects, with FDI ranging from 24 to 28%, suggesting their potential as alternatives for managing the red palm weevil. This research highlights the potential of lemongrass and gelam oils as environmentally friendly and effective alternatives to synthetic insecticides in combating the invasive red palm weevil.